Formulation and evaluation of lamivudine sustained release tablet using okra mucilage - Narahari N. Palei, Santhosh K. Mamidi, Jayaraman Rajangam (Journal of Applied Pharmaceutical Science, 2016)
The present study was to extract the mucilage from the Okra plant (Abelmoschus esculentus) and to study the effect of mucilage concentration on in vitro release of Lamivudine from it’s sustained release matrix tablets. Mucilage was extracted from the fruits of Abelmoschus esclentus using organic solvent Acetone. The extracted mucilage was subjected to various physiological properties for its suitability as an excipient in the preparation of tablet. Lamivudine sustained release tablets were prepared using different concentration of Okra mucilage as a sustained release matrix excipient. The formulated tablets were evaluated for post compression parameters such as weight variation, hardness, friability, wetting time, water absorption ratio, and in vitro drug release studies. Stability studies of optimized formulation were carried out for three months. The results of in vitro release revealed that the release rate decreased with increase in the concentration of mucilage. The release kinetics indicated that the nature of drug release from the matrix tablets was dependent on drug diffusion and polymer relaxation and therefore followed non-fickian or anomalous release. No incompatibility was observed between the drug and excipients used in the formulation of matrix tablets. The Okra mucilage showed promising results in terms of sustaining the release behavior of Lamivudine from the matrix. The developed sustained release tablets of Lamivudine, with extension of release up to 12 hours, can overcome all the disadvantages of conventional Lamivudine tablets.
Keywords: Lamivudine, Okra mucilage, sustained release, matrix tablet.